Influência da concentração de metabissulfito de sódio e tempo de exposição do camarão Litopenaeus vannamei (Boone,1931) - VIEIRA, Karla Patrícia Brito de Araújo (2006)
The aquaculture appears as activity of unquestionable relevance in the food production for the man. In this context, the shrimp culture if has detached as an activity of great yield, contributing for the economic growth of the agribusiness in the country. For being a noble alimentary product, the quality of the shrimps assumes basic importance being necessary the additive use to prevent the reaction of melanose`s (black spot). The sodium metabisulphite is the conservator of larger application in the shrimp culture; its use is supported in some effective legislation in the country, however, its main residue, the sulfur dioxide (SO2), when in high concentrations in the food health of the sensible consumers can provoke adverse reactions health of the sensible consumers. Of this form, it was objectified to improve the process of application of the sodium metabisulphite conservator in cultivated marine shrimps, contributing for the reduction of the residual text of this conservator, resulting in minimum and enough concentrations in the end item. Shrimps of the species Litopenaeus vannamei of classification 81/100, had been submitted the nine concentrations of sodium metabisulphite (1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5%), concomitant to the thermal shock, during five times of exposition (10, 15, 20, 25 and 30 min), correlating the concentration of the conservator and the time of immersion of the shrimps. The different methods of measure of the concentration of SO2 in the shrimps and the residual levels of SO2 in the frozen shrimps had been evaluated, during the period of eight weeks. Statistical analyzed results were being used multiple linear models. The shrimps submitted to concentration 1, 1.5, 2% had all presented good conservation during the period of storage under freezing, with satisfactory levels of SO2. The metabisulphite concentrations above of 2.5% had exceeded the maximum limits allowed by the current law for cooled and frozen shrimp (100 ppm of SO2 residual) being inappropriate for use in practice. The time of storage did not influence significantly (P<0.05) in the sulphite levels. The method of the adapted titration of Institute Adolfo Lutz presented great sensitivity for detection of free and combined sulphites, not occurring the same with the methods of the titration iodometric with and without heating and of the reactive ribbon with and without heating, in sensitivity order for free sulphites. It is concluded that the concentrations of sodium metabisulphite of currently used in the practical one are excessively high, causing conservator wastefulness and generating raised levels of SO2 in the shrimps.